Fault Simulation Research of Metro Gearbox based on Rigid-flexible Coupling - Xiaodan Huang; Bang Pei; He Guan; Xiangyang Qiao; Youhang Fan; Shipeng Song (Jixie chuandong)
Taking a subway gearbox in service in China as the research object，a computer virtual prototype is constructed and a rigid-flexible coupling model with a flexible gearbox is constructed by using finite element software，the vibration signal characteristics of different measuring points are discussed，and the vibration characteristics of the gearbox body are analyzed under the change conditions of the number of broken teeth，the torque and the speed. The results show that the closer the measuring point is to the axis，the more sensitive it is to the impact energy，but the relative frequency domain characteristics are fuzzy. The increase of the number of broken teeth，torque and speed will lead to the aggravation of vibration，and presents different vibration characteristics locally. The research results have certain reference value for the simulation and experimental research of subway gearbox.